Optimalisasi Produksi Lebah Madu Galo-Galo dengan Penanaman Vegetasi Berbunga di Sungkai, Kelurahan Lambung Bukik, Padang - Rusdimansyah Rusdimansyah; Hidrayani Hidrayani; Zahlul Ikhsan (Warta Pengabdian Andalas, 2023)
One of the things that can be done to increase production in Galo-Galo beekeeping is to plant flowering vegetation around the cultivation location. Some flower plants that are good for planting are Mexican Creeper, Xanthostemon, and Calliandra. These three plants can attract Galo-Galo honey bees to increase honey production. They will be able to improve the farmer's economy in Sungkai, Lambung Bukik Village, and Pauh Padang District. This community service activity aimed to provide understanding and flowering plant seeds to increase the production of Galo-Galo bee honey. The method used was counselling and practice. Planting flower vegetation was carried out in practice directly at the farm location. The activity resulted in 1) Increased partners' knowledge, interest, and skills in breeding Galo-Galo integrated with flowering vegetation. 2) Partners know and can increase the productivity of Galo-Galo bee honey. The activity ran smoothly, and the activity target was appropriately achieved. Farmers participating in the service have been able to cultivate stingless bees and optimize production by planting flowering vegetation.